Comparison of Frequency of Menorrhagia after Immediate Versus Delayed Intrauterine Contraception Device Insertion - Tasneem Akhter, Sarwat Faridi, Ghulam Zainab, Khiaynatsarwar Hashmi, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the incidence of menorrhagia after immediate post-partum versus delayed intrauterine contraception device insertion in local population. Place and Duration of Study: Department of Obstetrics & Gynecology, Bahawal Victoria Hospital, Bahawalpur from 1st January 2022 to 31st December 2022. Methodology: One hundred and ten women willing for intrauterine contraceptive device insertion of age 18-40 years were included. Females in which emergency hysterectomy was done, sepsis, premature rupture of membranes and fibroid uterus were excluded. Group A included the women in which intrauterine contraceptive device was inserted within 24 hours of delivery and Group B included the women in which intrauterine contraceptive device (IUCD) was inserted after 6 weeks of delivery. All patients were followed for 3 months for presence or absence of menorrhagia. Results: The mean age of women in group A was 28.67±5.72 years and in group B was 29.02±5.63 years. The mean parity in group A was 3.02±1.11 and in group B was 3.16±0.96. Menorrhagia in group A (immediate IUCD) was seen in 04 (7.27%) and in group B (delayed IUCD) was seen in 24 (25.45%) females with p-value of 0.010. Conclusion: There is less frequency of menorrhagia after immediate IUCD compared to delayed intrauterine contraception device insertion. Keywords: Intrauterine devices, Post-placental, Menorrhagia